2023
DOI: 10.3390/su15031994
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Forest Gap Research during 1980–2021

Abstract: (1) Background: Forest gaps play an important role in promoting forest regeneration and facilitating the forest growth cycle. Since the 1980s, forest gaps have been widely studied by forestry scientists. The purpose of this study was to review the global literature from 1980 to 2021, based on the scientific database Web of Science Core Collection, and to summarize the research hotspots and the trends of the forest gaps. (2) Method: A bibliometric analysis was performed using the visual analytic software CiteSp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The analysis of other articles, following similar a methodology, revealed that only one database is usually used for the application of bibliometric tools (e.g., [10,11]). The use of multiple databases can influence the results as the same article is likely to be found in multiple databases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of other articles, following similar a methodology, revealed that only one database is usually used for the application of bibliometric tools (e.g., [10,11]). The use of multiple databases can influence the results as the same article is likely to be found in multiple databases.…”
Section: Methodsmentioning
confidence: 99%
“…Keywords LIDAR (26); remote sensing (20); geographic information system (15); forest fire (12); ecology (11) Forest road (141); road construction (16); road ecology (15); soil (14); sustainable forest management (12); bearing capacity (10); stabilization (10); erosion control (8) Forest management (44); soil erosion (38); conservation (12); silviculture (12); biodiversity (10) Forest roads (245); erosion (50); sediment (24); runoff (22); sediment delivery (17); best management practices (14); rainfall simulation (10); forest hydrology (8) Forestry (44); forest operations (22); logging (16); productivity (14); optimization (12); harvesting (10); transportation (10) GIS (73); forest engineering (10); forest road maintenance (7); photogrammetry (7); forest road planning (6); terrestrial laser scanning (6) Water quality (30); forest road construction (13); forest harvesting (9); suspended sediment (6); environmental impacts (5); slope stability (5) Soil stabilization (11); planning (10); road density (10); forest planning (9); forest transportation (6); logging roads (6); ArcGIS (5) Recreation (20); design (10); construction (8); maintenance (7) 10…”
Section: Clustermentioning
confidence: 99%
“…Generally, for the period 1936-1980, the number of publications was flat at around 1-2 articles/year and then increased gradually until 1990 and increased significantly after 1990 (Figure 2). Referring to Xie et al (2023), the research trends can be divided into the initial, rapid, and deep development stages based on annual publication numbers. In this research, the initial stage was the period 1936-1980, the development stage was 1980-1990, and the rapid publication stage was 1990-2023.…”
Section: Research Trends Of Forests In Hungarymentioning
confidence: 99%
“…Bibliometric analysis in the forestry sectors has been applied to describe specific research trends, such as ecosystem services (Di Franco et al, 2021;Zhang et al, 2019), forest degradation (Aleixandre-Benavent et al, 2018), agroforestry practices (Leal et al, 2019), climate change (Araujo et al, 2023;Nam et al, 2022;Zhang et al, 2022), forestry big data (Gao et al, 2022), and forest bioeconomy (Jankovský et al 2021;Verma and Ghosh, 2023). Analyzing and mapping the bibliography can also use software such as the Bibliometrix R package (Gao et al, 2022;Zhang et al, 2022), Citespace (Li et al, 2022;Xie et al, 2023), and VOSviewer (Cheng et al, 2021;Hamidah et al, 2020;Singh, 2022;Soegoto et al, 2022). Each software package has advantages and disadvantages; therefore, the researcher's preference is essential in choosing the suitable bibliography analysis software.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a research method for assessing the productivity of authors, countries, and institutions by revealing their global distribution, collaboration, knowledge structures development trends [3,4], depth topics, citations, citation times, and keyword co-occurrence based on Web of Science (WoS) database. While many bibliometric studies have been carried out in different scientific fields such as medicine, computing, geography, environmental science, social science, water management, and animal sciences for different purposes (e.g., [3][4][5][6][7][8][9][10]), limited studies have been carried out in forestry (e.g., [11,12]). In addition, published papers related to seed orchards have not yet been subjected to bibliometric analysis.…”
Section: Introductionmentioning
confidence: 99%